Fraction B From Catfish Epidermal Secretions Kills Pancreatic Cancer Cells, Inhibits CD44 Expression and Stemness, and Alters Cancer Cell Metabolism - Al-Hassan, Jassim M.; Wei, Daoyan; Chakraborty, Sharmistha; Conway, Tara; Rhea, Patrea; Wei, Bo; Tran, Megan; Gagea, Mihai; Afzal, Mohammad; Oommen, Sosamma; Nair, Divya; Paul, Bincy M.; et al. (Frontiers in Pharmacology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is the fourth leading cause of cancer related death in western countries. The successful treatment of PDAC remained limited. We investigated the effect of Fraction B, a fraction containing proteins and lipids purified from catfish (Arius bilineatus, Val.) skin secretions on pancreatic ductal carcinoma (PDAC) both in-vivo and in-vitro. We report here that Fraction B potently suppressed the growth of both human/mouse derived pancreatic cancer cell lines in vitro and significantly reduced the growth of their relevant xenograft (Panc-02) and orthotopic tumor (human Panc-1 cells) (P < 0.05). The RPPA data obtained from the tumor tissue derived from orthotopic tumor bearing mice, treated with Fraction B shows that Fraction B alters the cancer stem cells related pathways and regulates glucose and glutamine metabolism. The down-regulation of the cancer stem cell markers CD44 expression was further confirmed in Panc-1 cells. CBC and blood chemistry analysis showed no systemic toxicity in Fraction B treated Panc-1 tumor bearing mice compared to that of control group. Our data supports that Fraction B is a potential candidate for PDAC treatment.